The Concept of Angles Formed by a Transversal in Indonesian Textbook: An External Didactic Transposition Study - Herizal Herizal; Nanang Priatna; Sufyani Prabawanto; Al Jupri (Mathematics Education Journal, 2026)
External didactic transposition plays an important role in shaping how mathematical concepts are represented in textbooks, potentially influencing students’ conceptual understanding. However, this process remains underexplored in Indonesian school textbooks. This study examined the transposition of angles formed by a transversal concept from scholarly knowledge to knowledge to be taught. Employing a qualitative textbook analysis approach, the study conducted a didactic transposition analysis by comparing three scholarly geometry textbooks with a mathematics textbook for seventh-grade students. Praxeological tools from the Anthropological Theory of Didactic was used to examine transformations in task types, techniques, technological discourse, and theoretical grounding. The study revealed significant transformations in the sequencing of content, conceptual depth, form of representation, and the epistemic goals. While scholarly sources introduce transversal angles in the context of any two lines, the school textbook restricts the context to parallel lines intersected by a transversal. This narrowing may result in epistemological obstacles, influencing students’ concept images toward overgeneralized or incomplete understandings. The findings highlight the need for mathematics educators to design tasks that introduce the concept from general to specific cases, and emphasize conceptual justification to prevent misconceptions. This study contributes novel insights to external didactic transposition through the underexplored case of angles formed by a transversal in Indonesian textbooks within the Anthropological Theory of the Didactic framework.